Thermal properties of spray-coated geopolymer-type compositions - Temuujin, Jadambaa; Minjigmaa, A; Rickard, William; Van Riessen, Arie (Kluwer Academic Publishers, 2012)
Thermal properties (DTA-TG and thermal expansion) of spray-coated fly ash-based geopolymer have been studied. The geopolymer composition selected for thermal spray coating had Si:Al = 3.3 and Na:Al = 1.45. To improve the fire resistant characteristics, fine- and coarse-milled vermiculite powder was added at 10 mass percent. Water:geopolymer ratios varied from 0.35 to 0.41 depending on vermiculite content and method of coating. Water added into a starting mixture to increase the flowability also decreased the geopolymerisation reaction.